2018
DOI: 10.1021/acsami.8b08232
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Capacitive Deionization Using Natural Basswood-Derived, Freestanding, Hierarchically Porous Carbon Electrodes

Abstract: Carbon electrodes are of great importance in constructing high-performance capacitive deionization (CDI) devices. However, the use of conventional carbon electrodes for CDI is limited because of their poor mechanical stability and low mass loading. Herein, we report a binder-free, freestanding, robust, and ultrathick carbon electrode derived from a wood carbon framework (WCF) for CDI applications. The WCF inherits the unique structure of natural basswood, containing straightly aligned channels interconnected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 61 publications
(163 reference statements)
1
54
0
Order By: Relevance
“…We observed an average SAC as high as 12.7 mg g À1 at 1.2 V with a corresponding L of 0.67, which is competitive with recently reported values for FT electrodes, naturally-based electrodes, and freestanding CDI electrodes. Recent reports for freestanding CDI electrodes developed from basswood 25 and commercially available AC 27 have observed a SAC of 5.7 mg g À1 and 8.9 mg g À1 with a L of 0.30 and 0.48, respectively. We also calculated the areal and volumetric SAC for our bread-derived electrodes.…”
Section: Performance Characterization Of Bread-derived Electrodes In mentioning
confidence: 97%
See 2 more Smart Citations
“…We observed an average SAC as high as 12.7 mg g À1 at 1.2 V with a corresponding L of 0.67, which is competitive with recently reported values for FT electrodes, naturally-based electrodes, and freestanding CDI electrodes. Recent reports for freestanding CDI electrodes developed from basswood 25 and commercially available AC 27 have observed a SAC of 5.7 mg g À1 and 8.9 mg g À1 with a L of 0.30 and 0.48, respectively. We also calculated the areal and volumetric SAC for our bread-derived electrodes.…”
Section: Performance Characterization Of Bread-derived Electrodes In mentioning
confidence: 97%
“…5 However, common electrode fabrication techniques using ACs require additional materials such as binders and current collecting mesh which can increase overall electrical resistance and material cost. [24][25][26] Reducing the material cost of the electrodes is a primary concern in CDI systems because it can be the largest expense in long-term full-scale operation. 26 Several recent studies have investigated the use of binder-free, freestanding electrodes to circumvent these issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clearly shown that they all possess the typical capacitor-like behaviour with no oxidation/reduction reactions; this suggests electrical double-layer behaviour as the main mechanism of ion adsorption on the surface of the electrodes. 19,35 Then, the specic capacitance of all electrodes was calculated, as shown in Fig. 2(b).…”
Section: Characterizationmentioning
confidence: 99%
“…To maximize the efficiency of MCDI, the as-prepared electrodes should have the required functionality without any insulating components; unfortunately, the application of most of the preparation methods for the current electrodes is hindered by the major drawbacks such as the use of polymer binders, which may block the pathway for ions and increase the internal resistance of the electrodes, severely limiting the salt removal capacity. [17][18][19] However, a radical improvement in electrode performance might be achieved if various free-standing three-dimensional (3D) structures could be developed via alternative ways. To date, several routes have been proposed to prepare 3D structures such as carbon aerogels, 20 graphene aerogels, 12,21 carbon nanotube/graphene hybrid sponges, 11 activated carbon nanobers, 10,22,23 and redox-active nanoparticles/graphene aerogels.…”
Section: Introductionmentioning
confidence: 99%